Poultry Litter Fertilization Impacts on Soil, Plant, and Water Characteristics in Loblolly Pine (Pinus taeda L.) Plantations and Silvopastures in the Mid-South USA - Blazier, Michael A.; Liechty, Hal O.; Gaston, Lewis A.; Ellum, Keith (IntechOpen, 2011)
None